FAMILY BUSINESS ACROSS GENERATION: A CASE STUDY - Maria Felecia Cindy H.; Aluisius Hery Pratono; Suyanto Suyanto (Perpustakaan Universitas Surabaya, 2018)
Abstract – This study aims to understand the family orientation concept for assessing the interaction between individual perceptions of family members and the company. This research discusses individual family members' family orientation in relation to the family business. The findings provide evidence howindividual family members relate to the family business. This incorporates five elements: family tradition, stability, loyalty, trust, and interdependency. This study contributes to extending the concept of family orientation by addressing the question of how individual family members relate to the family business.